A novel SLC20A2 nonsense variant and mechanistic studies of primary brain calcification - Yi Li; Lamei Yuan; Han Chen; Wen Zheng; Hongbo Xu; Zhijian Yang; Dan He; Hao Deng (PLoS ONE, 2026)
Primary brain calcification (PBC) is a rare neurodegenerative disease featured by bilateral brain calcifications and exhibiting high phenotypic and genetic heterogeneity. The clinical manifestations mainly include movement disorders, cognitive deficits, and neuropsychiatric symptoms. In this study, a novel heterozygous nonsense variant, c.1669C > T [p.(Gln557*)], in the solute carrier family 20 member 2 gene ( SLC20A2 ), encoding type III sodium-dependent inorganic phosphate transporter 2 (PiT2), was identified in a Han-Chinese family with PBC using whole exome sequencing and Sanger sequencing. Bioinformatics analysis predicted the variant’s deleterious effect. The cellular function impacts of the p.Gln557* variant and three other common PBC-related SLC20A2 variants, p.Ser113*, p.Ala585Thr, and p.Ser601Trp, were subsequently revealed. Subcellular localization analysis showed that the PiT2-Q557*, A585T, and S601W mutants mainly distributed in the plasma membrane and cytosol, whereas the PiT2-S113* mutant showed a diffuse distribution throughout the cells. All four investigated variants significantly impaired cellular inorganic phosphate transport activity. The protein mislocalization-inducing p.Ser113* variant likely causes haploinsufficiency, while the p.Gln557*, p.Ala585Thr, and p.Ser601Trp variants may lead to full or partial loss of function, or exert a dominant-negative effect. Cells expressing PiT2 mutants all exhibited inhibited proliferative and migratory activities, along with enhanced apoptosis. These SLC20A2 variants probably impair critical cellular functions, potentially providing an explanation for the neurological symptoms observed in PBC patients. These findings further broaden SLC20A2 variant spectrum and provide valuable mechanistic insights into the pathogenesis of SLC20A2 -associated PBC.